Advances in the management of upper tract urothelial carcinoma: improved endoscopic management through better diagnostics. Issue 12 (December 2018) - Knoedler, John J.; Raman, Jay D.
As a rare disease, the management of upper tract urothelial carcinoma (UTUC) continues to evolve. While radical nephroureterectomy remains the gold standard, there is a growing desire to pursue nephron-sparing approaches through endoscopic management, particularly for low-risk disease or in the setting of imperative indications. A particular challenge for those undertaking endoscopic management is appropriate grading and staging of tumors, and thereby appropriate patient selection. In this review we will cover the current state of diagnostics for UTUC as well as highlight the challenges in accurate diagnosis. Additionally, we will focus on emerging technologies to aid in optimizing diagnostic accuracy in UTUC. This will include discussion of narrow band imaging, photodynamic diagnosis, optical coherence tomography, and confocal laser endomicroscopy.